Acid beta-glucosidase/glucocerebrosidase (GCase) - Grabowski, Gregory (Henry Stewart Talks, 2007)
Properties of GCase: structure and function, Enzymology and cell biology of GCase, Requirements for GCase activity, GCase and its role in Gaucher disease, Genotype/Phenotype and molecular correlations, Therapies for Gaucher disease (enzymes, genes, chaperones)
Updated at 2016/07/27